Highly efficient production and simultaneous purification of d-tagatose through one-pot extraction-assisted isomerization of d-galactose - Guangzhen Wang; Xiaomei Lyu; Lu Wang; Mingming Wang; Ruijin Yang (Food Chemistry: X, 2023)
A one-pot extraction-assisted d-galactose-to-d-tagatose isomerization strategy was proposed based on the selective extraction of d-tagatose by phenylborate anions. 4-Vinylphenylboronic acid was selected with high extraction efficiency and selectivity towards d-tagatose. The extracted sugars could be desorbed through a two-staged stripping process with the purity of d-tagatose significantly increased. In-situ extraction-assisted d-galactose-to-d-tagatose isomerization was implemented for the first time ever reported, and the effect of boron-to-sugar ratio (boron: sugar) was investigated. The conversion yield of d-tagatose at 60 °C increased from ∼ 39 % (boron: sugar = 0.5) to ∼ 56 % (boron: sugar = 1) but then decreased to ∼ 44 % (boron: sugar = 1.5). With temperature increased to 70 °C, the conversion yield of d-tagatose was further improved to ∼ 61 % (boron: sugar = 1.5), with the minimized formation of byproducts. Moreover, high purity (∼83 %) and concentrated d-tagatose solution (∼40 g/L) was obtained after sequential desorption. The proposed extraction-assisted isomerization strategy achieved improving the yield and purity of d-tagatose, proving its feasibility in industrial applications.